Transformacja gospodarki polskiej po pięciu latach - 1989 - 1994 - Wilczyński, Wacław (Wydział Prawa i Administracji UAM, 1994)
The subject of the paper is a qualitative analysis and an attempt to evaluate the level of transformation of the Polish economy five years after the government stabilisation programme' was implemented at the end of 1989. The programme was also known as Leszek Balcerowicz's programme, who was deputy Prime Minister at the time. The essential question to be answered now is: to what extent have the basic pi-inciples of market economy (stable, convertible currency, market mechanisms as the main form of the functioning of the economy, and privatisation of the economy being the condition of a microeconomic rationality) have been implemented. The fact is that the private sector has gained a dominant position and therefore it can be said that the threshold towards market economy has been passed. And yet, the overall level of transformations is not satisfactory. A strong 'non-market' sector related to the state industiy, closed to market economy principles and demanding central planning is still there. It is also feared that this 'duality of systems' in which the state assumes the role of 'director' of an economic system based on two sets of principles, which obviously has a negative influence on the efficiency of any economic activity, will get even better established. High inflation and consequently expensive credit facilities discourage from investing; public finances deteriorate, public debt is increasing. The State has limited possibilities of action. What is more, there is a strong opposition to the privatisation of large state owned enterprises which continue to be centrally financed, regardless of their performance and results. All this clearly shows that the conditions of a successful completion of the transformation process in Poland are as follows: 1) the duality of systems has to be overcome, and the State must assume a role of a sovereign; 2) inflation must be combatted more efficiently and budgetaiy spending must be further reduced; 3) privatisation must be accelerated, and microeconomic rationality must be consistently implemented in the State sector. These are the necessary conditions for investment expansion and the economy being able to regain its capabilities of producing economic surplus.
Polish economy five years after the change